2019
DOI: 10.1371/journal.pone.0224726
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and immune profiling of metaplastic breast cancer: Correlation with survival

Abstract: The goal of this study is to characterize the genomic and immune profiles of metaplastic breast cancer (MpBC) and identify the association with survival through an analysis of archived tumor tissue. A next-generation sequencing-based mutational assay (Onco-48) was performed for 21 MpBC patients. Clinicopathologic characteristics were captured, including relapse free survival (RFS) and overall survival (OS). Immunohistochemistry (IHC) for CD3, CD4, CD8, and programmed death-ligand 1 (PD-L1) was also performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 23 publications
3
45
0
Order By: Relevance
“…Recent studies have identified mutations in the TP53, PI3K MAPK, RB1, and Wnt pathways as the most frequent somatic mutations in MBCs. [2][3][4][5][6][7][8][9][10][11] Our data confirm that spindle cell MBC shares similar molecular features with other morphologic subtypes of MBCs. 6,[9][10][11]23 PIK3CA mutations are particularly relevant because the ESMO Scale for Clinical Actionability of Molecular Targets (ESCAT) classified them as strong predictors of response to PIK3CA inhibitors (level IA) (see Supplemental Table 2 in the online version).…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Recent studies have identified mutations in the TP53, PI3K MAPK, RB1, and Wnt pathways as the most frequent somatic mutations in MBCs. [2][3][4][5][6][7][8][9][10][11] Our data confirm that spindle cell MBC shares similar molecular features with other morphologic subtypes of MBCs. 6,[9][10][11]23 PIK3CA mutations are particularly relevant because the ESMO Scale for Clinical Actionability of Molecular Targets (ESCAT) classified them as strong predictors of response to PIK3CA inhibitors (level IA) (see Supplemental Table 2 in the online version).…”
Section: Discussionsupporting
confidence: 64%
“…[2][3][4][5][6][7][8][9][10][11] Our data confirm that spindle cell MBC shares similar molecular features with other morphologic subtypes of MBCs. 6,[9][10][11]23 PIK3CA mutations are particularly relevant because the ESMO Scale for Clinical Actionability of Molecular Targets (ESCAT) classified them as strong predictors of response to PIK3CA inhibitors (level IA) (see Supplemental Table 2 in the online version). 24,25 Furthermore, the United States Food and Drug Administration (FDA) recently approved the PIK3CA inhibitor b Both cases were further tested by immunohistochemistry (CD117 and panTRK antibodies) and were negative.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations